Sustainable Production of Lignocellulolytic Enzymes in Solid-State Fermentation of Agro-Industrial Waste: Application in Pumpkin (Cucurbita maxima) Juice Clarification - Priya Rana; Baskaran Stephen Inbaraj; Sushma Gurumayum; Kandi Sridhar (Agronomy, 2021)
Valorization of agro-industrial waste through greener and biotechnological processes are promising approaches to minimize the generation of agro-industrial waste. Therefore, the study aimed to produce lignocellulolytic enzymes from agro-industrial waste under solid-state fermentation (SSF) conditions and study their application in the clarification of pumpkin juice. The SSF was performed with three different combinations of wheat bran + rice bran (WBRB), wheat bran + wheat straw (WBWS), and rice bran + wheat straw (RBWS) as dry solid substrates (1:1) using Fusarium oxysporum (MTCC 7229). The protein, carboxymethyl cellulase (CMCase), and xylanase contents ranged from 0.98–3.90 mg/g, 5.89–6.84 U/g substrate, and 10.08–13.77 U/g substrate, respectively in different agro-industrial waste as substrates (WBRB, WBWS, RBWS, and control). The increase in enzyme concentration (0.50–2.40%) added to pumpkin juice exhibited an increased juice yield (16.30–55.60%), reduced browning index (1.03–0.70), and an increase in clarity (5.31–13.77 %T), which was further confirmed by a total variance of 84.83% by principal component analysis. Thus, the low-cost lignocellulolytic enzymes can be produced from agro-industrial waste that might have applications in food and beverage industries. Hence, this approach could be used as a long-term sustainable and circular source to valorize agro-industrial waste towards the greener future and the preservation of ecosystems.